Periprosthetic Hip Fractures Outside the Initial Postoperative Period: Does Time from Diagnosis to Surgery Matter? - Bryan L. Scott, MD; Connor A. King, MD; Cody S. Lee, BS; Michael J. Lee, MD; Edwin P. Su, MD; David C. Landy, MD, PhD (Arthroplasty Today, 2020)
Background: Despite an increasing incidence and associated morbidity, the optimal timing for the surgical management of periprosthetic hip fractures remains unknown. This study sought to explore whether time to surgery was associated with medical or surgical complications. Methods: A retrospective review of Medicare data from 2010 to 2014 was performed using PearlDiver. All patients with a periprosthetic hip fracture greater than 90 days from surgery and undergoing open reduction internal fixation (ORIF) or revision total hip arthroplasty (RTHA) were included. Time to surgery was measured from diagnosis and dichotomized at 48 hours. Results: Of 342 patients undergoing ORIF, 269 (79%) had surgery within 48 hours. Of 255 patients undergoing RTHA, 142 (56%) had surgery within 48 hours. For ORIF, surgery more than 48 hours after diagnosis was associated with an increased rate of 30-day deep vein thrombosis or pulmonary embolism (15% vs 7%, P = .03), which remained after adjustment (odds ratio [OR]: 2.71, 95% confidence interval [CI]: 1.11-6.45). A similar association was seen for RTHA (12% vs 6%, P = .09 and OR: 2.61, 95% CI 1.01-7.24). For RTHA, surgery more than 48 hours after diagnosis was associated with an increased rate of 90-day periprosthetic joint infection (12% vs 4%, P = .007), which remained after adjustment (OR: 3.86, 95% CI: 1.36-12.72). A similar but not significant association was seen for ORIF (7% vs 3%, P = .18 and OR: 2.65, 95% CI: 0.73-8.91). Conclusions: Among Medicare patients with a periprosthetic hip fracture, time to surgery greater than 48 hours was associated with increased medical and surgical complications.